An increase in flow-diverter oversizing values as an independent risk factor for developing more severe in-stent stenosis. A retrospective single-center study based on flow diversion of supraclinoid internal carotid artery aneurysms - Vladev, Georgi; Sirakov, Alexander; Matanov, Svetozar; Sirakova, Kristina; Ninov, Kristian; Sirakov, Stanimir (Frontiers in Neurology, 2025)
IntroductionIn the past decade, flow diverters (FDs) have increasingly been used to treat cerebral aneurysms with unfavorable morphology in which other endovascular techniques fall short of being as effective. In-stent stenosis (ISS) is one of the most puzzling and frequent risks of flow diversion therapy observed on follow-ups. This complication, although mostly placid in its clinical course, can have dire consequences if patients become symptomatic. ISS is associated with many factors, none of which have been demonstrated to date to be solely responsible for the phenomenon.MethodsThis study was aimed at evaluating ISS incidence in patients in our clinic who were treated with flow-diverters for aneurysms, located on the supraclinoid segments of the internal carotid artery between September 2022 and May 2023. A retrospective analysis was conducted, which included 137 patients with a total of 142 aneurysms being treated. The main hypothesis was that oversizing of the implant might play a role in ISS development. The performed statistical analysis, aimed at finding a correlation between it and vessel lumen narrowing on the follow-ups. The effects of other known risk factors, such as sex, age, smoking, and hypertension, were also analyzed.ResultsStent oversizing with respect to the parent artery was positively correlated with subsequent ISS occurrence and severity. Older age was a protective factor against ISS. Patients who actively smoked had diminished risk of developing severe ISS.DiscussionStent oversizing can lead to ISS development, which might be more pronounced with larger implant-to-vessel sizing discrepancies. To achieve optimal results, the choice of implant diameter should consider all segments of the vessel in which it will be implanted. In cases of severe symptomatic ISS, continuation of dual anti-platelet therapy is a reasonable and effective option to address this complication.